STUDI PERENCANAAN PENGEMBANGAN PENYEDIAAN AIR BERSIH - Krisnayanti, Denik Sri; Udiana, I Made; Benu, Henry Jefrison (Jurnal Teknik Sipil, 2013)
The water is very important to human life. Human does not live without getting enough to water supply either in quantity and quality.The method used in the calculation projection of population that using aritmatic method and exponential method. The incresing of facilities and calculation projection which is analyzed by deviation standart and hidrolis analysis to pipeline that using software Waternet 2.2. Based on analysis and evaluation of the planning development in the first phase in 2021. It is founded the population of projection in District of East Kupang amounts 58.697 people. The water suplay is needed by domestic, namely home connection (SR) and public hydrant (HU) amounts 107,02 liter/sec and than the loss of water amounts 15%. Therefore, the requirements of water is founded to 8 villages namely 123,07 liters/sec. From the sources of water that is exis with minimum discharge 145 liters/sec, it is able to serve of requirement clean water in the servise area to 8 villsges in East Kupang District. The result of hydraulic analysis on pipeline plans uses software WaterNet 2.2 and there is no node that has a relative pressure under 10 meter. Therefore, the water can flow into each node within 24 hours. The maximum relative pressure occurs at node 51, it is 127,90 m in Naibonat Village. This is caused by the different of reservoir elevation with a service area until the pressure of relative getting high. The relative pressure can be derived using the PRV valve that is installed of the heigh in 68,39 m and then the lowest of relative pressure occurs at 74, namely 16,08 m in the Tuatuka Village. The highest energy loss occurs in the pipe 4 until 33,67 m at 08:00 O’clock AM wita. The maximum of flow velocity occours on pipe number 1,2,3 and 4 is equal 2,087 m/sec at 08:00 O’clock AM wita whereas the minimum of flow velocity occours on pipe 71 is equal 0,000 m/sec at 01:00 – 02:00 AM wita because of in the time there is no use at all.